Tuhan dalam Perdebatan Eksistensialisme - Wahyudi, Chafid (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
The philosophy of existentialism pays great attention to the fate of human beings as individualist embodiments. This also becomes a manifestation of human?s freedom which receives less attention due to its exclusion under the strong influence of Hegel?s doctrine essentialist philosophy or system of thought that emphasizes collectivity. The emergence of existentialism itself in turn propagates into the polemical invention of humans upon their God. There are two conceptions of the divine discourses on existentialism, namely the theistic existentialism and the atheistic one. Theistic existentialism tries to accept God and consider Him not to rob humans? freedom because God is understood individually, not as a self-enclosed system. On the contrary, atheistic existentialism actually rebels against God?s intervention in humans? freedom as well as eliminates the existence of God and brings the absolute freedom of human beings themselves, which in turn this leads to humans? creative activity.